Ekranisasi Memoar Imperfect karya Meira Anastasia dan Film Imperfect : Karir, Cinta dan Timbangan karya Sutradara Ernest Prakasa - Riani, Riska; Hasanuddin WS, Hasanuddin WS (Persona: Kajian Bahasa dan Sastra, 2024)
This research aims to describe how reductions, additions, and variations in changes in plot elements, setting, and characterization appear in the analysis The focus of this research is the memoir Imperfect, written by Meira Anastasia and published in 2018, as well as the film Imperfect: Career, Love and Scales, directed by Ernest Prakasa in 2019. This research is library research that uses qualitative descriptive methods. The data used in this research is all the content of the memoir and film. Meanwhile, the instruments used are the researchers themselves. The data collection technique was carried out by reading novels and watching films repeatedly, then identifying and classifying data related to the process of making films based on memoirs. Findings from this research include: (1) the subtraction aspect has 16 subtractions in the plot element, 1 subtraction in the setting element, and 7 subtractions in the characterization element of the memoir, (2) the addition aspect has 66 additions in the plot element, 7 additions in the setting element, and 25 additions in the characterization element of the film, (3) the variation change aspect has 12 changes in the plot element, 3 changes in the setting element, and 6 changes in the characterization element of the memoir.